The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1073/pnas.2021426118
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a body-wide photosensory array that matures in an adult-like animal and mediates eye–brain-independent movement and arousal

Abstract: The ability to respond to light has profoundly shaped life. Animals with eyes overwhelmingly rely on their visual circuits for mediating light-induced coordinated movements. Building on previously reported behaviors, we report the discovery of an organized, eye-independent (extraocular), body-wide photosensory framework that allows even a head-removed animal to move like an intact animal. Despite possessing sensitive cerebral eyes and a centralized brain that controls most behaviors, head-removed planarians sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 86 publications
(156 reference statements)
0
11
0
Order By: Relevance
“…24. Planarians respond to ultraviolet light through receptors existing at the surface throughout their body (Birkholz & Beane, 2017;Shettigar et al, 2021). Therefore, if planarian behaviors associated with eye-brain interaction are analyzed, ultraviolet light should be cut off (Figure 2a).…”
Section: Previous Versions Of Fiji R and Rstudio Compatible With Older Ormentioning
confidence: 99%
See 1 more Smart Citation
“…24. Planarians respond to ultraviolet light through receptors existing at the surface throughout their body (Birkholz & Beane, 2017;Shettigar et al, 2021). Therefore, if planarian behaviors associated with eye-brain interaction are analyzed, ultraviolet light should be cut off (Figure 2a).…”
Section: Previous Versions Of Fiji R and Rstudio Compatible With Older Ormentioning
confidence: 99%
“…To measure the body size of living planarians, use graph paper placed under a Petri dish. It can easily be confirmed whether planarians are undergoing regeneration or have regenerated by confirming whether the pharynx is positioned at the middle of the body. Planarians respond to ultraviolet light through receptors existing at the surface throughout their body (Birkholz & Beane, 2017; Shettigar et al., 2021). Therefore, if planarian behaviors associated with eye‐brain interaction are analyzed, ultraviolet light should be cut off (Figure 2a).…”
Section: Tipsmentioning
confidence: 99%
“…This is also the case for planarian flatworms, free-living members of the phylum Platyhelminthes, which not only display chemotactic behavior, but also respond to differences in temperature, contact, light, and water flow (Miyamoto and Shimozawa, 1985;Umesono et al, 2011;Inoue et al, 2015;Inoue, 2017;Ross et al, 2018). Although planarians can respond to light of different wavelengths (Paskin et al, 2014;Shettigar et al, 2017;Shettigar et al, 2021), they are not known to detect shapes (Walter, 1907). The sensory systems of planarians are well-integrated with their central nervous system (Agata et al, 1998;Okamoto et al, 2005;Inoue et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…For example, it was shown that ciliary gliding depends on serotonergic signaling ( Currie and Pearson, 2013 ), that peristalsis and scrunching are distinct gaits ( Cochet-Escartin et al, 2015 ), with peristalsis resulting from non-functional cilia ( Rompolas et al, 2010 ) and scrunching being a cilia-independent escape gait ( Cochet-Escartin et al, 2015 ). Thermotaxis, phototaxis and chemotaxis have been found to require the presence of a brain to sense their respective stimuli ( Inoue et al, 2015 ), whereas fission ( Malinowski et al, 2017 ; Goel et al, 2021 ), scrunching ( Cochet-Escartin et al, 2015 ) and avoidance of local near-ultraviolet light stimulation ( Paskin et al, 2014 ; Shettigar et al, 2017 ; Le et al, 2021 ; Shettigar et al, 2021 ) can occur without a brain.…”
Section: Introductionmentioning
confidence: 99%